2009
DOI: 10.1080/00207590701607930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of received and mobilized support on recipients' and providers' self‐efficacy beliefs: A 1‐year follow‐up study with patients receiving radical prostatectomy and their spouses

Abstract: From a proactive agentic perspective, social support is not just seen as a protective cushion against environmental demands. Rather, support may facilitate an individual's self-regulation by enhancing perceived self-efficacy (i.e., enabling hypothesis). In the present study, patient-reported indicators of mobilized and received spousal support as predictors of their own and their spouses' self-efficacy beliefs were investigated within 1 year following radical prostatectomy. During this time frame, postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
10
1
3
Order By: Relevance
“…Consistent with other literature, the men in this study relied on their partner for emotional support, and this means that partners have to manage not only their own anxiety but also the distress of their husbands [25]. Furthermore, our findings suggest that support between men and partners becomes inequitable during treatment and remains the same 6 months later (in contrast to [16]). While perceptions of stigma were not cited as direct causes of social isolation, partner's reluctance to disclose prostate-related issues to others likely contributed to the degree of social isolation they reported feeling.…”
Section: Comparison To Prior Literaturesupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with other literature, the men in this study relied on their partner for emotional support, and this means that partners have to manage not only their own anxiety but also the distress of their husbands [25]. Furthermore, our findings suggest that support between men and partners becomes inequitable during treatment and remains the same 6 months later (in contrast to [16]). While perceptions of stigma were not cited as direct causes of social isolation, partner's reluctance to disclose prostate-related issues to others likely contributed to the degree of social isolation they reported feeling.…”
Section: Comparison To Prior Literaturesupporting
confidence: 86%
“…Supportive interaction has been associated with better recovery [13,14], differentially associated with higher well-being in both patients and partners (e.g. [15]), and related to higher relationship satisfaction [16]. Therefore, understanding the coupled experience of giving and receiving support following a prostate cancer diagnosis may help us to identify those who are at high risk of inadequate support provision.…”
mentioning
confidence: 99%
“…Authors found that patients’ support mobilisation efforts were positively associated with their own self‐efficacy beliefs. Predicting change in self‐efficacy over a 1‐year time lag in prostate cancer survivors and their partners, Knoll, Scholz, Burkert, Roigas, and Gralla () found neither survivor‐reported receipt of partner support nor their support mobilisation efforts prior to tumor surgery associated with their own self‐efficacy beliefs 12 months later. However, patients’ pre‐surgery support mobilisation was related with increases in their partners’ self‐efficacy 1 year later.…”
Section: Introductionmentioning
confidence: 99%
“…Pain self‐efficacy is therefore thought to be a robust predictor of the adjustment to vulvo‐vaginal pain. It has been shown that social support and partner support promoted self‐efficacy . The subjective experience of intimacy in a romantic relationship could help one to feel supported and provide a positive context to increase self‐efficacy, which is crucial in mobilizing women to engage in proactive coping behaviors.…”
Section: Introductionmentioning
confidence: 99%